Strategi Kepala Sekolah dalam Meningkatkan Kualitas Pembelajaran Melalui Pengembangan Sarana Prasarana - Mihmidaty Ya’cub; Dewy Suwanti Ga’a (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2021)
The principal as a manager or leader must have a strategy in developing educational facilities and infrastructure. Educational facilities and infrastructure are one of important resources in supporting the learning process in schools. The purpose of this article is to describe the principal's strategy in improving infrastructure through the development of infrastructure. This article is qualitative field research. The form of the research is descriptive qualitative with the design of data collection techniques through observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis. The results of this article found that the principal's strategy in improving the quality of learning through the development of infrastructure at (Public High School) SMA Negeri 1 Jombang was quite effective and efficient, especially seen from the presence of CCTV facilities that made it easier for the principal to control the teachers, as well as students during the learning process and LCD can understand the material presented by the teachers. The principal strategy in developing infrastructure is through the planning stages of infrastructure, organizing infrastructure, mobilizing infrastructure, and controlling infrastructure. The conclusion from the explanation above is that the principal's strategy in improving the quality of learning through the development of infrastructure at SMA Negeri 1 Jombang seen from the CCTV and LCD facilities is quite good because after seeing the results achieved, it has fulfilled the objectives to be achieved, namely to improve the quality of learning.